Ateneo come fonte di Stefano di Bisanzio - Leonardo Fiorentini (Annali Online dell'Università di Ferrara. Sezione Lettere, 2016)
Const. Adm. 23, 40-43 depends on Steph. Byz Ι 19 in which there is an original version of Ath. II 44b.